Discursos do Museu da Língua Portuguesa: uma língua em movimento nas práticas culturais brasileiras - Santos, Wilmihara Benevides da Silva Alves dos (2019)
This research had as objective to reflect the discursive positions of the Museum of the Portuguese Language as intangible heritage policy. From the descriptive analysis of eleven thematic videos located at the Grande Galeria on second floor of this museum sought to highlight what was excessively seen and silenced, said and denied about the linguistic and cultural practices lived in the Brazilian territory. Based on this framework, we see how the option for certain statements puts a policy of truth into play, that is, a way of seeing Portuguese as an expression of Brazilian culture. The research procedures are based on Michel Foucault's analytical tools